Survei Minat Siswa SMA Kristen 1 Amahai Terhadap Pembelajaran Pendidikan Jasmani Di Era Pandemi Covid - -, Minita; Anaktototy, Jacob; Rumahlewang, Emma (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2022)
This study aims to determine how much SMA Kristen 1 Amahai students’ interest in learning physical education in the COVID pandemic era Survey research was used to collect information by compiling statements submitted to respondents. The population in this study were students of SMA Kristen 1 Amahai class XII IIs/MIA, which consisted of 3 classes with a total of 100 students. With the number of each class, namely: class MIA 1 (33 students), class MIA II (32 students), and class IIS (a total of 35 students), sampling was done randomly. The data was collected using a questionnaire. Test the validity of the instrument using product-moment correlation and reliability tests using the Cronbach alpha formula. The results of research on SMA Kristen 1 Amahai students’ interest in learning physical education in the COVID pandemic era are as follows: 19 students (31.67%) got an average score, 34 students (11.67%) got a good score, and 7 students (11.67%) scored below the average. The data shows that students' interest in learning is quite high for online learning during the pandemic.